2017
DOI: 10.1108/tqm-11-2016-0102
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of lean supply chain: an empirical research on the effect of context

Abstract: Purpose The purpose of this paper is to empirically investigate the effect of a set of contextual variables on the implementation of lean supply chain (LSC) practices. The authors do that by investigating one main research question: “how do the contextual variables (i.e. plant size, supply chain level, level of onshore suppliers and age of the LM initiative) influence on the degree of adoption of LSC practices?” Design/methodology/approach To this end, the authors collected data from 115 companies from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 58 publications
5
64
2
Order By: Relevance
“…For instance, Marodin et al (2016) found that firms situated in the top tiers of an ASC, closer to the end customer, were more likely to be adopting lean practices relative to those firms located in the lower tiers of an ASC, which supports the findings of Boonsthonsatit & Jungthawan (2015). Tortorella et al (2017a) sided with this, as findings from their study revealed firms positioned closer to the customer implemented lean practices to a greater extent when compared with firms positioned lower down the ASC. On the contrary, Sezen at al.…”
Section: Supply Chain Positional Tiermentioning
confidence: 55%
See 2 more Smart Citations
“…For instance, Marodin et al (2016) found that firms situated in the top tiers of an ASC, closer to the end customer, were more likely to be adopting lean practices relative to those firms located in the lower tiers of an ASC, which supports the findings of Boonsthonsatit & Jungthawan (2015). Tortorella et al (2017a) sided with this, as findings from their study revealed firms positioned closer to the customer implemented lean practices to a greater extent when compared with firms positioned lower down the ASC. On the contrary, Sezen at al.…”
Section: Supply Chain Positional Tiermentioning
confidence: 55%
“…There is limited research examining lean and agile production relative to the role of contextual factors, especially supply chain positional tier (Jasti & Kodali, 2015;Marodin et al, 2016;Tortorella et al, 2017aTortorella et al, , 2017b. Furthermore, there are inconsistent results presented in the literature Negrao et al (2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Includes impact of lean on organizational performance including operational performance, financial performance etc. (Bhasin, 2008;Fullerton & Wempe, 2009;Belekoukias, Garza-Reyes & Kumar, 2014;Uhrin, Bruque-Camara & Moyano-Fuentes, 2017;Negrão et al, 2017) Leanness Includes research papers that discuss leanness assessment or measurement (Papadopoulou & Özbayrak, 2005;Singh, Garg & Sharma, 2010;Vinodh & Kumar-Chintha, 2011;Ram-Matawale, Datta & Sankar-Mahapatra, 2014) Lean supply Chain Includes papers that discuss adoption of lean principles, concepts, tools and techniques throughout the entire supply chain aimed at elimination of waste and non-value-added activities from the overall value stream in the supply chain (Stentoft-Arlbjørn, Vagn-Freytag & de Haas, 2011;Ma, Wang & Xu, 2011;Jasti & Kodali, 2015a;Tortorella, Miorando & Tlapa, 2017) Lean and other value creation tools Includes papers which discuss lean and other process improvement methodologies like TQM, Six sigma, Agile (Dahlgaard & Dahlgaard Park, 2006;Naslund, 2008;De Koeijer, Paauwe & -Huijsman, 2014;Mehrsai, Thoben & Scholz-Reiter, 2014) Lean Epistemology…”
Section: Lean Adoptionmentioning
confidence: 99%
“…The core thrust of lean in SCP is to reduce wastes in order to create a streamlined and highly efficient system that produces at customer demand pace (Shah & Ward, 2003). Differently from single firm planning, Lean in SCP needs to consider that the different links of the SC may be far off each other and have different ownerships (Tortorella, Miorando, & Tlapa, 2017). Lamming (1996) and Liker and Wu (2000) compared operations practices used along supply chains by lean Japanese automakers and not-lean automakers (Lamming, 1996;Liker & Wu, 2000).…”
Section: Lean Management-based Scp Model (Lean-p)mentioning
confidence: 99%